University residences in Italy: comparison between four projects - Adolfo F. L. Baratta; Claudio Piferi (Agathón)
Recently, the construction policy of the Italian universities has been characterized by a complex implementation process aimed at rebalancing structural equipment and meeting previous and current needs. From this point of view, many existing and new buildings have been acquired by the Universities to solve the shortcomings of student reception and the international mobility. The contribution describes four experiences of design research and realization of university residences, promoted by the Luigi Bocconi University of Milan, IUAV of Venice, Florence University and Salerno University: different situations that reiterate how much programming and design affect the overall quality of a University.